TUMBUHAN PANGAN DAN PEMETAANNYA DI HUTAN TAMAN GUMI BANTEN DESA WANAGIRI BULELENG BALI - Wijana, Nyoman; Mulyadiharja, Sanusi; Bestari, Ida Ayu Purnama (Prosiding Seminar Nasional Biologi, 2021)
Taman Gumi Banten Forest is located in Wanagiri Village, Sukasada District, Buleleng Regency. In the forest is composed of various species of plants that can be used as material for various purposes. One of the forest products can be used as food. The purpose of this study was to determine the various plant species used by the Wanagiri village community and a map of their distribution in their natural ecosystem. The population of this research is all plant species in the forest of Taman Gumi Banten. The research sample for (1) the mapping study is the entire forest area of ​​Taman Gumi Banten. (2) Samples of plant species are all plant species covered by a square. Sum of squares is 86 squares. There were 25 people who were used as informants. Data were analyzed descriptively. The results showed: (1) There were a total of 67 plant species in the forest of Taman Gumi Banten. Of the 67 existing species, there are as many as 60 species (86.76%) which are considered useful plants, while 7 species (13.24%) are not yet known for their use. (2) Of the 60 species of useful plants, which can be utilized by the people, most of them are used as ceremonial facilities as many as 27 species (45%), board 23 species (38.3%), food 22 species (36.6% ), medicine 12 species (20%), and industry 2 species (3.3%). There are 22 species of useful plants for food needs. Parts of plants that are used include the fruit, seeds, flowers and leaves. (4) From the mapping results, it appears that the distribution of food plant species is evenly distributed in the two research zones and the direction of the north-south spatial distribution is also evenly distributed.